Virna Glaucoma Drainage Device Implantation On Pediatric Patient With Steroid Induced Glaucoma: Poster Presentation - Case Report - Resident - CHRISTIAN ANDREW DARIAN SIANIPAR; Fidalia; Sari, Prima Maya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Steroid-induced Glaucoma (SIG) in pediatric patient is reported to have a more progressive and severe manifestations often unresponsive to glaucoma filtration surgery. We aim to report a successful management of SIG using Virna implant on pediatric patient. Case Illustration : A 10 years old boy underwent bilateral Virna GDD implantation following uncontrollable IOP after multiple trabeculectomies. The patient presented with a UCVA of 4/60 on both eyes. IOP of RE and LE is 31.8 mmHg and 29.7 mmHg respectively with four anti-glaucoma medications. Both eyes revealed conjunctival hyperemia with no bleb formation, VH3 AC, 12 o’clock iridectomy, C/D ratio of 0.9 with bayonet sign and nasalization on indirect funduscope, open angle on gonioscope, annular scotoma on Humphrey, and diffuse thinning of RNFL on OCT. Six months postoperatively, BCVA of RE and LE is 6/60 and 6/30 respectively with minimal progression on both ocular visual field defects. As for IOP, RE IOP is 18.7 mmHg with two anti-glaucoma medications and LE IOP is 14.3 mmHg without anti-glaucoma medications. Discussion : Multiple failed trabeculectomies is an indication for GDD. Virna implants are meant for adult subsequently making plate and tube placement crucial in pediatric patient because the globe is still growing and relatively thin. It is necessary to evaluate IOP periodically after implantation as IOP will enter hypertensive phase and stabilize in 3-6 months. Conclusion : GDD implantation, including Virna Implant, is a viable alternative to children with refractory SIG to prevent further glaucomatous damage.